Distance Education and MOOCs for Language Learning in China - Du, Weihua; Ge, Shili (Learning Technologies and Systems, 2021)
Massive open online course (MOOC) is an online learning tool, especially for distance learning. It has attracted a great deal of attention by higher education institution around the globe. It gave rise to academic discussion on MOOC impact, design and research. However, researches on MOOC’s impact on language learning are still lacking. Based on the analysis of the external and internal defects of MOOCs, this paper attempts to analyze the methods to solve these defects and put forward some methods, such as paying equal attention to business and knowledge goal, arranging teaching plan reasonably, arranging teacher-student ratio, and adopting multidimensional formative evaluation, to promote the development of Chinese foreign language MOOCs.